Metal-organic frameworks with pyridyl-based isophthalic acid and their catalytic applications in microwave assisted peroxidative oxidation of alcohols and Henry reaction - Karmakar, Anirban (2019)
Reactions of 5-{(pyridin-4-ylmethyl)amino} isophthalic acid (H(2)L1) with copper(II), zinc(II), and cadmium(II) were studied, and the obtained metal organic frameworks (MOFs) [{Cu(L1)(DMF)}center dot DMF center dot H2O](n) (1), [Zn(L1)(H2O)(n) (2), and [Cd(L1)](n) (3) were characterized by elemental analysis, Fourier transform infrared spectroscopy, and X-ray single-crystal diffraction. As shown by X-ray crystallography, novel hybrid organic inorganic coordination-driven assemblies were obtained which exhibit different two- and three-dimensional (2D and 3D) polymeric architectures. Compounds 1 and 2 have 2D structures, whereas compound 3 features a 3D network type polymer with a dimetallic core acting as a secondary building unit. These frameworks act as heterogeneous polymeric solid catalysts (the most effective one being the copper MOF 1) for solvent-free microwave assisted peroxidative oxidation of primary and secondary alcohols. They also effectively catalyze the nitroaldol (Henry) reaction of different aldehydes with nitroalkanes in water. These MOF-based heterogeneous catalysts can be easily recovered and reused, at least for a few consecutive cycles, without losing activity.